The Chemopreventive Role of β-Elemene in Cholangiocarcinoma by Restoring PCDH9 Expression - Wu, Qing; Shi, Xintong; Pan, Yating; Liao, Xinyi; Xu, Jiahua; Gu, Xiaoqiang; Yu, Wenlong; Chen, Ying; Yu, Guanzhen (Frontiers in Oncology, 2022)
Background β-Elemene, an effective anticancer component isolated from the Chinese herbal medicine Rhizoma Zedoariae, has been proved to have therapeutic potential against multiple cancers by extensive clinical trials and experimental research. However, its preventive role in cholangiocarcinoma (CCA) and the mechanisms of action of β-elemene on CCA need to be further investigated. Methods A thioacetamide (TAA)-induced pre-CCA animal model was well-established, and a low dosage of β-elemene was intragastrically (i.g.) administered for 6 months. Livers were harvested and examined histologically by a deep-learning convolutional neural network (CNN). cDNA array was used to analyze the genetic changes of CCA cells following β-elemene treatment. Immunohistochemical methods were applied to detect β-elemene-targeted protein PCDH9 in CCA specimens, and its predictive role was analyzed. β-Elemene treatment at the cellular or animal level was performed to test the effect of this traditional Chinese medicine on CCA cells. Results In the rat model of pre-CCA, the ratio of cholangiolar proliferation lesions was 0.98% ± 0.72% in the control group, significantly higher than that of the β-elemene (0. 47% ± 0.30%) groups (p = 0.0471). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that the top 10 pathways affected by β-elemene treatment were associated with energy metabolism, and one was associated with the cell cycle. β-Elemene inactivated a number of oncogenes and restored the expression of multiple tumor suppressors. PCDH9 is a target of β-elemene and displays an important role in predicting tumor recurrence in CCA patients. Conclusions These findings proved that long-term use of β-elemene has the potential to interrupt the progression of CCA and improve the life quality of rats. Moreover, β-elemene exerted its anticancer potential partially by restoring the expression of PCDH9.